2023
DOI: 10.1002/advs.202206187
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Nanoparticles Deliver the Therapeutic VEGFA mRNA In Vitro and In Vivo and Transform Extracellular Vesicles for Their Functional Extensions

Abstract: Lipid nanoparticles (LNPs) are currently used to transport functional mRNAs, such as COVID-19 mRNA vaccines. The delivery of angiogenic molecules, such as therapeutic VEGF-A mRNA, to ischemic tissues for producing new blood vessels is an emerging strategy for the treatment of cardiovascular diseases. Here, the authors deliver VEGF-A mRNA via LNPs and study stoichiometric quantification of their uptake kinetics and how the transport of exogenous LNP-mRNAs between cells is functionally extended by cells' own veh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…The authors further pointed out that large quantities of PTEN mRNA-containing exosomes were produced, and following systemic injection, displayed an increased survival rate in PTEN-deficient glioma mouse models [ 104 ]. Importantly, a novel pre-secretory drug-loading technique was developed by Nawaz et al using lipid nanoparticles [ 105 ]. The authors delivered a therapeutic agent, VEGF-A mRNA, via lipid nanoparticles and studied the uptake kinetics and transport of the exogenous nanoparticles [ 105 ].…”
Section: Exosomal Drug Delivery: Solutionsmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors further pointed out that large quantities of PTEN mRNA-containing exosomes were produced, and following systemic injection, displayed an increased survival rate in PTEN-deficient glioma mouse models [ 104 ]. Importantly, a novel pre-secretory drug-loading technique was developed by Nawaz et al using lipid nanoparticles [ 105 ]. The authors delivered a therapeutic agent, VEGF-A mRNA, via lipid nanoparticles and studied the uptake kinetics and transport of the exogenous nanoparticles [ 105 ].…”
Section: Exosomal Drug Delivery: Solutionsmentioning
confidence: 99%
“…Importantly, a novel pre-secretory drug-loading technique was developed by Nawaz et al using lipid nanoparticles [ 105 ]. The authors delivered a therapeutic agent, VEGF-A mRNA, via lipid nanoparticles and studied the uptake kinetics and transport of the exogenous nanoparticles [ 105 ]. The results showed that the lipid nanoparticles altered the exosomes as functional extensions to distribute the therapeutic agent among cells [ 105 ].…”
Section: Exosomal Drug Delivery: Solutionsmentioning
confidence: 99%
See 3 more Smart Citations